Identification of smut resistance in wild arachis species and its introgression into peanut elite lines - De Blas, Francisco J.; Bressano, Marina; Teich, Ingrid; Balzarini, Mónica; Arias, Reneé; Manifesto, Maria Marcela; Costero, Beatriz P.; Oddino, Claudio; Soave, Sara J.; Soave, Juan A.; Buteler, Mario I.; Massa, Alicia N.; et al. (Crop Science Society of America, 2019)
Peanut smut caused by Thecaphora frezii Carranza & Lindquist has been an issue for farmers and the peanut industry (Arachis hypogaea L.) in Argentina since the mid-1990s. This disease causes pod malformation due to hypertrophy of seed tissues; in addition, colonized cells filled with teliospores give seeds a smutted mass appearance. Incidence may reach up to 52% in commercial plots, with up to 35% yield losses. Cultural management strategies and chemical treatment have not been effective; therefore, growing resistant varieties is likely to be the most effective control method for this disease. This study is aimed to identify sources of resistance in wild Arachis and to develop pre-breeding materials for transferring the trait to cultivated peanut. After 3 yr of field trials using a randomized complete block design, the seven accessions of wild species assayed were resistant to smut. An amphidiploid [A. correntina (Burkart) Krapov. & W.C. Greg. × A. cardenasii Krapov. & W.C. Greg.] × A. batizocoi Krapov. & W.C. Greg.)4× was obtained and subsequently crossed with and experimental line of A. hypogaea for the development of a recombinant inbred line (RIL) population (89 lines). The RIL population showed a high phenotypic variability for resistance to peanut smut. The amphidiploid and 22 RILs were highly resistant, illustrating the effective transmission of resistance to peanut smut from the wild diploids into A. hypogaea. The development of RILs with resistance derived from wild species is a significant step towards the development of new peanut cultivars with different sources of resistance to peanut smut.